Analisis Profitabilitas BUMDES Karya Bersama - Bakhtiar Ass, Syamsul; Paharuddin, Hardianti; Chair, Ummul; Safrin, Abdul; Bohari, Bohari; Ikbal, Muhammad (Movere Journal, 2025)
This study aims to determine the profitability of BUMDes in 2016-2022. This study uses a quantitative descriptive analysis method using primary and secondary data sources with library research and field research data collection techniques, Return on Assets (ROA) and Return on Equity (ROE) data analysis techniques. The results of the study show that financial performance seen from the profitability of BUMDes for 7 years is categorized as good, because the average Return on Equity (ROE) has met the industry standard of 40%. Although Return on Assets (ROA) is not good, because the average calculation is still far below the industry standard Return on Assets (ROA) of 30%, the high Return on Equity (ROE) results can cover these shortcomings.